2018
DOI: 10.1111/1749-4877.12288
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rewilding, species introductions and climate change on the structure and function of the Yukon boreal forest ecosystem

Abstract: Community and ecosystem changes are happening in the pristine boreal forest ecosystem of the Yukon for 2 reasons. First, climate change is affecting the abiotic environment (temperature, rainfall and growing season) and driving changes in plant productivity and predator–prey interactions. Second, simultaneously change is occurring because of mammal species reintroductions and rewilding. The key ecological question is the impact these faunal changes will have on trophic dynamics. Primary productivity in the bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…However, food supplementation experiments revealed that supplemental food had little or no effect on snowshoe hare reproduction, survival, or population growth (O’Donoghue and Krebs , Krebs et al , Krebs et al ). Furthermore, winter shrub biomass in Kluane has been increasing because of climate change over the last three decades (Boonstra et al ); however, there has been no concomitant improvement in hare reproductive output during this period. Second, chronic stress due to predator chases could potentially depress reproduction during the decline and low phases.…”
Section: Discussionmentioning
confidence: 99%
“…However, food supplementation experiments revealed that supplemental food had little or no effect on snowshoe hare reproduction, survival, or population growth (O’Donoghue and Krebs , Krebs et al , Krebs et al ). Furthermore, winter shrub biomass in Kluane has been increasing because of climate change over the last three decades (Boonstra et al ); however, there has been no concomitant improvement in hare reproductive output during this period. Second, chronic stress due to predator chases could potentially depress reproduction during the decline and low phases.…”
Section: Discussionmentioning
confidence: 99%
“…The harvest of Canada lynx, grizzly and black bears, moose, caribou, and thin-horn sheep are co-managed by First Nations and other governments with a conservation objective. Given the problems that large mammals face in most parts of the Earth, our area is again a contrast at present (Ripple et al 2014;Boonstra et al 2018) because none of these large mammal species are under threat.…”
Section: Discussionmentioning
confidence: 99%
“…Winter temperatures (November to April) have been increasing on average since 1970 by 0.47 °C per decade (see Fig. 2 in Boonstra et al 2018). Summer temperatures during the growing season are increasing more slowly, at 0.26 ºC per decade ( Fig.…”
Section: Climate Change In the Kluane Regionmentioning
confidence: 95%
See 1 more Smart Citation
“…). Earth's climate is changing; climate change will inevitably affect the distribution and abundance of many plant and animal species via changes in the abiotic environment, primary productivity and species interactions (Boonstra et al. ). There exists some evidence that climate change may dampen the dynamics of some cyclic rodent populations (e.g.…”
Section: What Have We Learned and Where Do We Go From Here?mentioning
confidence: 99%